WOMEN CASUAL CLOTHES WITH TEACHING BATIK MOTIF PRINCE OF SAMUDRA AT MOUNT KEMUKUS - Wati, Bintang Kusuma; Andini, Bertha Galuh (Indonesian Institute of the Arts Surakarta, 2023)
Prince Samudra teachings on Mount Kemukus covering agriculture, culture, martial arts and Islamic religious knowledge are works of art that are applied to adult women's casual clothing, with this final project the author wants to bring and introduce to the general public through fashion trends. The process of creating a work starts from the exploration stage (searching for sources of ideas, concepts, and the basis for creation), design (the design of the work), and embodiment (making the work). The process of making works of art goes through the initial stages of making designs, making patterns, preparing tools and materials, scraping, printing, dyeing colors. sewing and finishing. The technique used in this work is hand-drawn batik using night wax as the main tool, canting, primisima cloth